Caloric restriction protects from acute and chronic kidney injury by inhibiting monocyte recruitment - Paolo Molinari; Alberto Verlato; Johan Noble; Sara Alibrandi; Sofia Bin; Katja Ferrari; Paolo Malvezzi; Carlo Alfieri; Giuseppe Castellano; Laura Perin; Valter Longo; Paolo Cravedi (iScience)
Summary: Diet influences disease progression, yet the effects of fasting on acute kidney injury (AKI) and its transition to chronic kidney disease (CKD) remain unclear. This study evaluated fasting-mimicking diet (FMD) cycles versus ad libitum feeding in murine models of AKI and CKD induced by aristolochic acid or folic acid. FMD significantly reduced serum creatinine, kidney injury, and maladaptive repair marker expression, and promoted faster recovery. It also lowered renal cytokines and pro-fibrotic genes, reduced CCL2 levels, and decreased monocyte recruitment while favoring protective monocyte phenotypes. Cycles of caloric restriction yielded similar nephroprotection. Initiating FMD at the peak of AKI enhanced repair and attenuated inflammation. Inhibition of CCR2 abolished FMD’s protective effects, implicating the CCL2/CCR2 axis in mediating its benefits. However, broader anti-inflammatory actions may also contribute, and reduced CCL2 may reflect downstream effects. These findings highlight the potential of dietary interventions to modulate kidney injury and inflammation in AKI and CKD.